KEGIATAN PELATIHAN PEMBUATAN BAHAN AJAR BERBASIS ONLINE BAGI GURU-GURU SD MA’ARIF KETEGAN - Khudzaifah, Muhammad; Fannani, Bakhruddin (JRCE (Journal of Research on Community Engagement), 2022)
During the Covid-19 emergency, schools have implemented learning activities in the midst of an emergency according to the conditions and creativity of each school, where students learn from home with guidance from teachers and parents. In this activity, it is directed to achieve the objectives of this training, the instructors get additional knowledge of knowledge about making interactive online-based multimedia learning media and can create interactive online-based multimedia learning media. The methods applied in this activity are direct training and practice. In this training, several activities will be given including the presentation of material and the practice of making media by the training participants. Furthermore, the learning media that has been done by the teachers are presented in front of the class to provide input to each other for the improvement of the learning media that has been made. The result of this activity is a YouTube channel containing instructional videos made by SD Ma'arif Ketegan teachers.